Context is everything: reflections on CLIL in the UK. Issue 5 (2nd September 2020) - Dobson, Alan
ABSTRACT: Content and Language Integrated Learning (CLIL), involving teaching one or more subjects through the medium of the foreign language, is widespread in Europe, but only offered in a sprinkling of UK schools. Sustainability has been a persistent issue since the 1970s. The focus here is on England but various issues will be familiar to colleagues in other parts of the UK. The article traces CLIL's sporadic development, initiatives taken to support it, and the distinctive challenges it faces. The implementation issues are quite different from those in mainland Europe, where successful CLIL is usually associated with conditions rarely encountered in the UK. CLIL in Europe is almost synonymous with teaching through the medium of English; no other language has this standing in the UK, with the exception of those areas where Gaelic- or Welsh-medium education is well established. The article considers how some form of CLIL might be implemented in the UK and ways of supporting it in the context of national policies. The author draws on his perspective as one who was present when significant initiatives were proposed in the European Union, the Council of Europe and the UK.